A shape to the microlithic Robberg from Elands Bay Cave (South Africa) - (:unkn) unknown (My University, 2016)
Elands Bay Cave (EBC) is a key South African site allowing discussion of technological change and adaptations that occurred from the Upper Pleniglacial to the Holocene. In 2011, we set out a new field campaign aiming to clarify the nature and chronology of the earliest Robberg occupations at the site, a technocomplex whose appearance closely relates to the Last Glacial Maximum. Our results document the appearance of the Robberg technology at ca. 19 398-18 790 cal BP, succeeding a phase commonly referred to as the Early Later Stone Age. In this paper, we further develop the definition of the Robberg by providing a technological and functional study of the MOS1 lithic assemblage at EBC, dated to 14 605-14 278 cal BP. Our results show that EBC occupants dominantly selected local quartz in addition to heat-treated silcrete that was introduced from distances greater than 30 km. Robberg inhabitants applied different reduction strategies combining bipolar/anvil and soft stone hammer percussion. Reduction sequences were oriented toward the production of a set of small artefacts (< 25 mm long) that can be generically classified as bladelets. The low incidence of retouched forms and the absence of geometrics, together with our functional study, testify to a flexible composite microlithic technology. We also discuss the raw material provisioning strategies of EBC Robberg inhabitants and develop the question of the intra-and inter-assemblages variability. Finally, we attempt to discuss its temporal trends and conclude on the originality of the Robberg technology within the context of other Late Pleistocene microlithic traditions.
Keywords: African Research